Symmetrical and asymmetrical dimethylarginine as predictors for mortality in patients referred for coronary angiography: the Ludwigshafen risk and cardiovascular health study - Meinitzer, Andreas; Kielstein, Jan T; Pilz, Stefan; Drechsler, Christiane; Ritz, Eberhard; Boehm, Bernhard O; Winkelmann, Bernhard R; März, Winfried (Clinical chemistry, 2011)
Asymmetrical dimethylarginine (ADMA), an endogenous nitric oxide synthase inhibitor, has been linked to cardiovascular risk. The clinical role of its structural isomer symmetrical dimethylarginine (SDMA) remains largely unclear.We measured SDMA and ADMA in 3229 patients undergoing coronary angiography at baseline (1997-2000) and recorded total and cardiovascular mortality during a median follow-up time of 7.7 years. We investigated associations of SDMA with cardiovascular risk factors and mortality and compared its role as a cardiovascular risk factor with ADMA, which predicted mortality in previous analyses of our study.In linear regression analyses including common cardiovascular risk factors as covariates, SDMA and ADMA were significantly associated with cystatin C, N-terminal pro-B-type natriuretic peptide, New York Heart Association classification, and homocysteine. The regression coefficients were higher for SDMA than for ADMA. In Cox proportional-hazards models adjusted for cardiovascular risk factors, the hazard ratios (HRs) (with 95% CI) in the second, third, and fourth SDMA quartile compared to the lowest quartile were 0.77 (0.60-0.99), 0.99 (0.78-1.25), and 1.51 (1.20-1.91) for total mortality and 0.92 (0.68-1.25), 0.93 (0.68-1.26), and 1.54 (1.14-2.01) for cardiovascular mortality. The same calculations for ADMA quartiles revealed HRs of 1.05 (0.83-1.32), 1.19 (0.95-1.50), and 1.61 (1.30-1.99) for total mortality and HR of 1.00 (0.74-1.34), 1.26 (0.95-1.68), and 1.54 (1.18-2.02) for cardiovascular mortality.Serum concentrations of SDMA are independently associated with increased cardiovascular and all-cause mortality in patients undergoing coronary angiography. The pattern of risk linked to SDMA is different from that linked to ADMA, suggesting different pathophysiological roles of these 2 methylarginine metabolites.